Shapes of cell signaling. Issue 27 (September 2021) - Linding, Rune; Klipp, Edda
Abstract: Cell signaling is a complex process organized in time and space. Signal transduction is constantly modulated by cell-intrinsic and cell-extrinsic input cues and the resulting phenotypic responses such as morphological can feed back into the system. This provides cells with a responsive, accurate, and rugged system to deal with changes in the surroundings or the genome. Whilst signaling networks (dynamic transient protein–protein interactions modulated by post-translational modifications in response to input cues) have been researched for decades, further analysis of their spatial organization is critical for both basic and disease biology and will benefit from recent advances in computational modeling and image analysis using deep/machine learning and in microscopy and imaging. Furthermore, mathematical modeling with reaction-diffusion approaches on time-varying geometries complements the investigations, allowing to conceptualize the organizational principles of signaling and information transduction in the four dimensions of time and space. Highlights: Signaling is organized in time, space, and context. Cell shape and signaling networks can be mirror images. Imaging and mathematical models support understanding of signaling. Deep hidden physics offers potential for global mechanistic analysis of dynamic signaling systems. Morphology and spatially associated cell signaling are critical for understanding of complex diseases.